Male Servants in Russia in the Second Half of the 19th – at the Beginning of the 20th Century: from Domestics to Workmen’s Cooperative Association: Мужская прислуга в России второй половины XIX – начала ХХ века: от дворни к артели - Veremenko, Valentina; Lubov, Samarina (Przegląd Wschodnioeuropejski, 2020)
The article analyzes the changes occurred as a result of the abolition of serfdom in the position of persons who were in service. Status and responsibilities of male domestics is characterized, attention is drawn to the patriarchal-family nature of relationships between masters and servants. In the post-reform period owners were more interested in cheapness and lack of specialization of domestic servants, which resulted in a significant reduction of the male part of it. At the same time, it was impossible to completely abandon the services of male employees. As a result, there was a need to hire these people for temporary work. For the male servants considerable benefits were provided by formation of comradely associations, artels, functioning in accordance with their charters. This system, unlike personal hiring, has changed the functions and status of each employee. The level of responsibility has risen, financial obligations have appeared, but also guarantees emerged: for customers guarantees of high-quality performance of work, for performers guaranteed payment, clearly defined amount of work, protection of honor and dignity. A new form of social production has formed – the service industry.